A biotechnology perspective of fungal proteases - Souza, Paula Monteiro de (2015)
Proteases hydrolyze the peptide bonds of proteins into peptides and amino acids, being found in all living organisms, and are essential for cell growth and differentiation. Proteolytic enzymes have potential application in a wide number of industrial processes such as food, laundry detergent and pharmaceutical. Proteases from microbial sources have dominated applications in industrial sectors. Fungal proteases are used for hydrolyzing protein and other components of soy beans and wheat in soy sauce production. Proteases can be produced in large quantities in a short time by established methods of fermentation. The parameters such as variation in C/N ratio, presence of some sugars, besides several other physical factors are important in the development of fermentation process. Proteases of fungal origin can be produced cost effectively, have an advantage faster production, the ease with which the enzymes can be modified and mycelium can be easily removed by filtration. The production of proteases has been carried out using submerged fermentation, but conditions in solid state fermentation lead to several potential advantages for the production of fungal enzymes. This review focuses on the production of fungal proteases, their distribution, structural-functional aspects, physical and chemical parameters, and the use of these enzymes in industrial applications.